The history of formation and development of the National Museum of Roman Art in Mérida (Spain) - K.G. Gorshkova; O.A. Masalova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The article is devoted to the history of preservation of the archaeological monuments of the city of Mérida that keep the memory of the former greatness of the capital of the Roman province of Lusitania. The Archaeological Museum of Merida was founded under the Royal Decree of 1836. Subsequently, it transformed from a small collection of local artworks into the National Museum of Roman Art, i.e., it was recognized and declared as being of national importance. On July 10, 1975, the Royal Decree was adopted to open the National Museum of Roman Art in Mérida. The latter became the first museum to receive the national status outside the Spanish capital of Madrid. Its collections and activities revolve around the Roman period, to which a permanent exhibition in a new specially designed building is dedicated. The Visigothic collection is housed in a separate building of the Santa Clara Church, for which a new exhibition space is currently being planned. The history of the museum’s collections is inseparable from the work of people who made a great contribution both to the replenishment of the funds and to the evolution of the exposition discourse. The museum has embarked on a rich research program to study and popularize Roman history and culture. By continuing as the National Center for the Study of the Roman World, it remains true to the original research task. Therefore, the National Museum of Roman Art in Mérida can be defined as the largest cultural center of all aspects of the daily life of Augusta Emerita, one of the main cities on the western border of the Roman Empire.